IMPROVEMENT OF THE ENDURANCE MOTOR SKILL IN ELITE QWAN KI DO ATHLETES - Cojocariu Adrian; Ungurean Bogdan; Oprean Alexadnru (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The aim of the present study is to put in evidence the effects of some physical training means from preparatory phase on some forms of endurance in Qwan Ki Do martial art. We started from the hypothesis that using an efficient planning and adequate means it is possible the improving of general endurance and the static force-endurance combination in lower limbs in Qwan Ki Do (maintaining a specific position named Trung Binh Tan). The experiment was performed during 4 weeks. In the study it was included 12 male athletes from Romanian Qwan Ki Do national team, which was found in the preparatory phase for participating in European Championships 2013. The results reveal a very significant progress in both tests, suggesting that an adequate programme could conduct to the improvement of aerobic capacity, which could be an important support in athletes training for competition specific effort.